Industrial training report: Forest Research Institute Malaysia / Najiha Md Yusof - Md Yusof, Najiha (Universiti Teknologi MARA, Negeri Sembilan, 2021)
This report describes the internship I spent at the Forest Research Institute Malaysia (PRIM). The main objective of the Internship Report is to fulfil the partial requirements for course Industrial Training (IMC690) for Bachelor of Information Science (Hons.) Library Management. It is the output of the five (5) month long internship in the PRIM Library. An internship is a great way to gain hands-on experience with any real-world idea. Internships put theory and experience together in every field of study. Therefore, it clarifies the students' theoretical concepts, which might not be achievable through teaching sessions and follow-up tests. After completing the internship programme, I gained ample experience in the acquisition, collection, and distribution of library reading materials, as well as managerial activities, reference services, and the preservation of old manu scripts, which I have outlined in various chapters of the report. There are also some observations from my viewpoint that I feel would be useful to the authority in improving the PRIM Library.